Comparing Chromosomes between Cucumber (Cucumis sativus L.) and Melon (C. melo L.) Based on Amino Acids Analysis - Meshal M. Almutairi; Hany M. Almotairy (Food Science and Agriculture: Research Highlights Vol. 1, 2025)
Cucumis sative has evolved from Cucumis melon through chromosome fusions, but details of these fusions are unknown. This research aimed to compare the genome sequences in both cucurbit crops by analyzing amino acids in their chromosomes. The data of GC%, relative codon bias strength (RCBS), and modified relative codon bias (MRCBS) were computed, and a cluster analysis was used to place each similar chromosome into one cluster. The result revealed some higher values of GC% in cucumber, such as chromosomes 19, 14, and 9, with 43.16, 43.06, and 40.45, respectively, while melon had some higher GC% values such as 45.97 and 42.90 in chromosomes 2 and 9, respectively. The higher means of RSCU (0.5) were asparagine, aspartic acid, and cysteine in both cucurbit crops. The values of the MRCBS had similar groups for both crops. This first group was glutamine, lysine, glycine, leucine, phenylalanine, valine, asparagine, tyrosine, stop codon, glutamic acid, and cysteine. The average linkage was higher in aspartic acid (GAT) at both cultivars. The polygenetic tree had eight clusters, with seq2 and seq21 as the first cluster at 0.79 in both crops. These findings would help plant breeders develop growth habits for both cultivars during the breeding program.